QAS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A new phase has been reached in the decentralisation of CTA s former Question-and-Answer Service (QAS), with the establishment of the Nigerian Agricultural Question and Answer Service (NAQAS). Hosted by the National Agricultural Extension and...